Education on Religious Moderation in Entrop-Jayapura Subdistrict through the Moderation Village Assisted by STAKPN-Sentani - Kabanga, Lewi; Malatuny, Yakob Godlif; Syafaat Siahaan, Daniel; Pardomuan, Gusti N; Labobar, Yohanes K; M. Kopeuw, Pilipus (Abdi Masyarakat, 2024)
Religious-based conflicts arise in diverse societies and tend to be triggered by simpler issues that expand into large-scale conflicts in the name of religion. The aim of this community service is to build solidarity and tolerance among the community as a form of anticipation against religiously nuanced conflicts in Entrop, Jayapura City. This community service is framed in the form of a religious moderation village initiated by STAKPN-Sentani. The method applied in this community service has gone through several stages, such as observation and interviews, FGD (focus group discussions) as the core activity, the declaration of the moderation village, and the preparation of reports. The outcomes achieved from this initiative include the development of an understanding of religious conflict mitigation based on religious teachings, where this mitigation involves comprehension of quotes from each religion's holy scriptures. Additionally, the culmination of this activity is the establishment of the religious moderation village guided by STAKPN-Sentani in Entrop. Religious conflict mitigation in Entrop is closely related to the discourse in holy scriptures and the involvement of religious higher education, due to the framework of the community's condition. It is hoped that through this initiative, a sense of tolerance among religious communities can be fostered to create an always conducive atmosphere.